Isolated distant lymph node metastases in ovarian cancer. Should a new substage be created? - Dimitrios Nasioudis; Emily M. Ko; Ashley F. Haggerty; Robert L. Giuntoli, II; Robert A. Burger; Mark A. Morgan; Nawar A. Latif (Elsevier, 2019)
Abstact: Objective: To evaluate the prognostic significance of isolated distant lymph node metastases in comparison to other metastatic sites and stage IIIC disease. Methods: The National Cancer Data Base was accessed and patients diagnosed between 2004 and 2014 with stage IV or IIIC epithelial ovarian cancer who met criteria for pathological staging were identified. Overall survival (OS) was calculated with Kaplan-Meier curves and compared with the log-rank test. A Cox model was constructed to control for confounders. Results: A total of 33,561 patients met the inclusion criteria; 582 (1.7%) had stage IV only due to distant lymph node metastases (stage IV-LN), 8130 (24.2%) had stage IV with other sites of distant metastases (stage IV-other) and 24,849 (75.4%) had stage IIIC disease. The median OS for patients with stage IV-LN was 42.41 months (95% CI: 37.59, 47.23) compared to 30.23 months (95% CI: 29.30, 31.16) for those with stage IV-other (p < .001) and 45.57 (95% CI: 44.86, 46.28) for those with stage IIIC disease (p = .54). On multivariate analysis, patients with stage IV-other had a worse survival (HR: 1.41, 95% CI: 1.27, 1.57) compared to those with stage IV-LN. There was no statistically significant difference in survival between patients with stage IV-LN and stage IIIC disease (HR: 1.00, CI: 0.90, 1.11, p = .99). Conclusions: Isolated distant LN metastases is associated with better survival compared to stage IV disease due to other metastatic sites and comparable to patients with stage IIIC disease. Keywords: Ovary, Cancer, Stage IV, Lymph nodes, Metastasis